Pelatihan Tarjamah untuk Peningkatan Kompetensi Bahasa Arab Santri Pondok Pesantren Al Mandily Panyabungan - Hakim, Rani Ismil; Darman, Isra Hayati; Oktarina, Hanifah (Warta Pengabdian Andalas, 2025)
This community service project on Arabic translation training at Al-Mandiliy Islamic Boarding School, Panyabungan, Mandailing Natal, aimed to improve students’ proficiency in Arabic, with a focus on translation skills. Utilizing the Participatory Action Research (PAR) approach, the program actively involved students and teachers in identifying problems, planning solutions, implementing training, and conducting joint evaluations. The training consisted of several phases: problem identification, participatory planning, interactive implementation, reflection, joint evaluation, and sustainable follow-up. The results demonstrated significant improvement in students' understanding of Arabic-to-Indonesian translation techniques and strategies, particularly in conveying meaning within appropriate contextual frameworks. Despite these gains, challenges such as limited vocabulary, inadequate grammar mastery, over-reliance on literal translation, and difficulty in constructing well-formed Indonesian sentences were observed. Reflection and evaluation phases revealed substantial progress in the students' translation competence. Overall, the training not only enhanced the students' Arabic skills but also contributed to the broader improvement of educational quality at the boarding school. These outcomes are essential for strengthening students’ capacity to comprehend Islamic texts and prepare them for academic, religious, and social responsibilities.